Pengaruh Keharmonisan Keluarga terhadap Kegiatan Belajar Siswa di SMK Negeri 9 Kabupaten Bungo - Wiwin Ariga; Akmal Sutja; Hera Wahyuni (Departement of Mathematics Education, 2023)
The purpose of this study to uncover how much the influence of family harmony to student learning activities. This study is limited to the harmony of families seen from the communication factor and learning activities. This research uses a type of quantitative descriptive research with survey method approach with the students of the class X, XI in SMK Negeri 9 Bungo Regency. SAMPULES A study of 79 students were determined using Simple Random Sampling technique. Data collection is done by using a questionnaire. The data obtained were analyzed by using a percentage and correlation technique. The results of the analysis prove that family harmony is at the level with a percentage of 85%, and student learning activities are at the level with a percentage of 85%. Hypothesis testing proves that the variable of the harmony of the mains (x) of 0.847 or may be expressed as linear equations Y = 12,521 + 9.132 X. In that table value t of voltage by 13.977 compared to T table dk = n-1 = 77 amounted to 1,6649 with SIG = 0.00 then the harmony of families affect the learning activities. And indicating that the R value is the correlation found 0.853 and the sw sw drief won 0.727 or (72.7%) This indicates that the percentage of the independent variable of the effect of the independent variable (X) on the dependent variable (Y) of 72.7%. These findings provide implications to guidance and counseling in school to become more active and sensitive to see the development of students while at school. Overall educational roles can reduce the problems facing students not only in school but out schools, communities and families who may impact the optimization of learning activities so as to achieve good future goals.